Ethical Leadership and Employee’s Performance in Lagos State Government-Office of the Auditor General - Ayobami Elegunde; Olufunke Tayo Omolara; Motunrayo Abimbola (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2023)
Ethical leadership is leadership that is directed by respect for ethical beliefs and values and for the dignity and rights of others. This study examined the effects of ethical leadership on employee performance in Lagos State Government-Office of Auditor General. The objectives of the study were to: examine the effect of ethical leadership on employee effectiveness in Lagos State Government-Office of the Auditor General; investigate the effect of ethical leadership on employee job satisfaction in Lagos State Government-Office of the Auditor General and evaluate the influence of ethical leadership on employee productivity in Lagos State Government-Office of the Auditor General. The study adopted a descriptive survey research design on a population of 381 of Lagos State Government-Office of Auditor General. Purposive sampling technique was employed in administering the research instrument. The research instrument employed was a questionnaire. Data were gathered from primary source. The research instrument employed was a self-constructed 5-point Likert scale questionnaire. The research instrument was validated through content validity and a Cronbach alpha reliability test of 0.875, 0.895 and 0.823 indexes were conducted. The results of the study revealed that ethical leadership has a significant influence on employee effectiveness, job satisfaction and productivity. Thus, the study recommended that the leadership of the commission should adopt equal treatment of its staff to help improve the quality and increase employees’ sense of commitment towards their job.